2020
DOI: 10.1055/s-0039-1690821
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Active Methylene Isocyanides with α-Oxodithioesters Induced by Base: An Expedient Synthesis of 4-Methylthio/Ethoxycarbonyl-5-acylthiazoles

Abstract: Cyclization of tosylmethyl isocyanide with α-oxodithioesters in the presence of KOH is reported for the synthesis of 4-methylthio-5-acylthiazoles. Similarly, ethyl isocyanoacetate underwent cyclization with α-oxodithioesters to form 4-ethoxycarbonyl-5-acylthiazoles in the presence of DBU/EtOH. Mechanisms for the formation of thiazoles are proposed. These thiazoles can also be obtained by Takeda reaction, in which thiazole-4,5-anhydride is acylated with aromatic compounds followed by esterification; however, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…As a reference compound, doxorubicin was used. The evaluation revealed that disubstituted compounds 2,4-dichloro (74d) and 3,4-dichloro (74h) displayed the best activity against four tumor cell lines (NCI-H292, HEp-2, HT- 29 Thus, the presence of di-Cl substitution was beneficial for cytotoxic activity. Compound 74b with an electron withdrawal group (4-NO 2 ) was found to be more active against NCI-H292 with an IC 50 of 7.41 ± 1.37 µM than 74c with a 3-NO 2 group (IC 50 of 22.77 ± 2.77 µM), indicating the importance of not only the nature but also of the position of the substituent at the thiazole ring as far as the activity is concerned.…”
Section: Thiazole Derivatives As Anticancer Agentsmentioning
confidence: 99%
“…As a reference compound, doxorubicin was used. The evaluation revealed that disubstituted compounds 2,4-dichloro (74d) and 3,4-dichloro (74h) displayed the best activity against four tumor cell lines (NCI-H292, HEp-2, HT- 29 Thus, the presence of di-Cl substitution was beneficial for cytotoxic activity. Compound 74b with an electron withdrawal group (4-NO 2 ) was found to be more active against NCI-H292 with an IC 50 of 7.41 ± 1.37 µM than 74c with a 3-NO 2 group (IC 50 of 22.77 ± 2.77 µM), indicating the importance of not only the nature but also of the position of the substituent at the thiazole ring as far as the activity is concerned.…”
Section: Thiazole Derivatives As Anticancer Agentsmentioning
confidence: 99%
“…In 2020, Sadashiva and co‐workers put forth the synthesis of 4‐methylthio‐5‐acylthiazoles 98 and 4‐ethoxycarbonyl‐5‐acylthiazole 99 by cyclization of tosylmethyl isocyanide 55 and ethyl isocyanoacetate respectively [83] . The reaction conditions showcase considerable substrate scope, irrespective of the electronic nature of the functional groups present on the α ‐oxodithioester (Scheme 55).…”
Section: Synthesis Of Thiazolesmentioning
confidence: 99%
“…More recently, an efficient cyclization reaction produced 4‐methylthio‐5‐acylthiazoles from a reaction of isocyanoacetate and α‐oxodithioester in the presence of DBU/ethanol (Figure 1C). [25] …”
Section: Introductionmentioning
confidence: 99%
“…More recently, an efficient cyclization reaction produced 4-methylthio-5-acylthiazoles from a reaction of isocyanoacetate and α-oxodithioester in the presence of DBU/ethanol (Figure 1C). [25] Another attractive pharmacophore for drug discovery is chalcone. 1,3-Diphenyl-2-propen-1-ones are α, β-unsaturated carbonyl compounds with two aromatic rings attached, known as chalcones or chalconoids.…”
Section: Introductionmentioning
confidence: 99%